The challenges of hepatitis C management in Iran: A qualitative study with patients. (3rd November 2019) - Behzadifar, Masoud; Azari, Samad; Gorji, Hasan Abolghasem; Rezapour, Aziz; Bragazzi, Nicola Luigi
Summary: Background: The patient's perspective concerning the treatment process and the knowledge of the challenges and problems that they encounter can help to improve their treatment conditions. Aim: The present study aimed at analyzing the experiences of hepatitis C virus (HCV) patients in Iran and the challenges encountered during the management and treatment process. Methods: Semi‐structured in‐depth and face‐to‐face interviews were conducted. The criteria for selecting patients were as follows: HCV‐positive subjects, with confirmed diagnosis of HCV, and under treatment. Content analysis was used to analyze the data. MAXQDA Ver11 software was used to better manage data. This study is based on the "Consolidated Criteria for Reporting Qualitative Research" (COREQ) checklist. Results: Twenty‐one HCV patients were interviewed. The mean age of participants was 36.14 ± 11.29 years. Seven themes with 20 subthemes emerged from the content analysis of the interviews, namely, (a) disease‐related stigma, (b) lack of knowledge, (c) psychological problems, (d) financial problems, (e) complications of treatment, (f) lack of family and community support, and (g) health‐care system. Conclusion: The findings of this study showed that a range of economic, social, and cultural problems could affect the treatment of HCV patients. Health policy and decision makers should try to provide them with a better management.